PENGARUH BENTUK SABUNGAN DAN JUMLAH PAKU TERHADAP KEKUATAN SAMBUNGAN KAYU - Marolop Sinaga (Jurnal Penelitian Hasil Hutan, 1994)
The form of joint and the amount of fastener have important role in wood engineering especially for the strength of timber jointing. An investigation on the influence of joint-form using nails as fastener had been conducted. There are three treatment of joint-fonns, i,e.: V-joint, the hooked scarf joint and but joint. Two treatment of the amount of nails as fastener use are two and four nails. The strenght test was conducted according to ASTM standard.The results of investigation show that :1. The highest value of modulus of elasticity (MOE) is produced by the treatment combination of hooked scarf joint and two nails as fastener with the value of 148,082 kg/cm2.2. The treatment combination of hooked scarf joint with two and four nails as fastener produced quite high value of modulus of rupture (MOR) of 1.520 and 1,593 kg/cm2,respectively.3. The hooked scarf joint is generally better then the V-joint or butt joint.